Is the method of localizing intraocular foreign bodies according to Madroszkiewicz still outstanding ? - Rospond, Iwona; Sosnowski, Piotr; Pecold, Krystyna (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Nowadays, in available methods of visualizing and localizing intraocular foreign bodies, apart from ultrasonography, a special stress is laid on computed tomography. Classic radiological method of Mądroszkiewicz – in which the X-rays of the orbit is made after putting up the special indicators under the conjunctiva – seems to be neglected considering those more advanced diagnostic methods. The aim of this study is to prove the undoubtful novelty of this method together with ultrasonography, in comparison with computed tomography on the grounds of 2 cases, presenting the patients successfully treated at the Department of Ophtalmology, University of Medical Sciences, Poznań, Poland.